Plant Salinity Sensors: Current Understanding and Future Directions - Wang, Cheng-Feng; Han, Guo-Liang; Yang, Zong-Ran; Li, Yu-Xia; Wang, Bao-Shan (Frontiers in Plant Science, 2022)
Salt stress is one of the main factors limiting plant growth and crop yield. High salinity generates two unfavorable conditions affecting plant roots: osmotic stress, which disturbs root growth and metabolism in the initial phase; and ionic stress, which induces a series of deleterious changes in growth and metabolism in the second phase. Plants have evolved various sensors or receptors to sense osmotic and ionic stresses to initiate salt signal transduction and adaptation. Therefore, salt-stress sensors or receptors are of great significance in plant response to salt stress and are attracting increasing research attention. In the past decade, much progress has been made in uncovering the sensors involved in salt stress. Here, we focus on the reported osmotic sensors and Na+ sensors and their signal transduction pathways in plant roots under salt stress. Through bioinformatic analyses we also predicted the structures and possible mechanisms of candidate sensors. Understanding how plants perceive salt stress is not only helpful to improve plant salt tolerance, reduce the restriction of salt stress on crop growth, and then promote the development of agriculture, but also has far-reaching significance for scientists to deeply understand the field of stress environment.